Comprehensive quality assessment of Xiaoer Chiqiao Qingre granules by fingerprinting technology combined with multi-component quantitative methods - Zhao, Liping; Sun, Xiangfei; Yan, Hui; Sun, Guoxiang (Journal of Chromatography A, 2025)
•Developed and established FTIR and DSC quantized fingerprints of XCQG.•Peak purity was checked using dual-wavelength absorbance coefficient ratio spectra (DWAR).•First application of QAMS and MAML for multicomponent quantification of XCQG.•Comprehensive linear quantitative fingerprint method (CLQFM) was used to quality evaluation. To enhance the safety, efficacy, and quality consistency of herbal compound preparation (HCP), 20 batches of Xiaoer Chiqiao Qingre granules (XCQG) were selected as the research subject, and established a comprehensive evaluation strategy for the quality of XCQG. Firstly, the fingerprint peaks of XCQG at two wavelengths were recorded, and the purity of the fingerprint peaks was analyzed by dual-wavelength absorbance coefficient ratio spectrum (DWAR). Subsequently, quantitative analysis of multi-components by single marker (QAMS) and multi-markers assay by monolinear method (MAML) were employed to determine the content of the four major compounds of XCQG and fit the obtained results. The results showed that both methods correlated excellent with standard curve method (SCM). Furthermore, differential scanning calorimetry (DSC) and fourier transform infrared (FTIR) spectroscopy quantized fingerprinting (QFP) were developed to investigate complete thermal change and structural analysis of components. The comprehensive linear quantitative fingerprint method (CLQFM) was developed to evaluate fingerprints, enabling successful qualitative and quantitative classification of all samples into distinct quality grades. Overall, this study promotes the dual control of fingerprint peak purity and thermal stability of XCQG, while offering scientific insights into its chemical properties.